2023
DOI: 10.5435/jaaos-d-22-00060
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Glenoid Bone Loss and Instability: An Evidence-based Approach to Diagnosis and Management

Abstract: Posterior glenohumeral instability is an underappreciated cause of disability that may necessitate surgical intervention to allow functional glenoid restoration. However, posterior glenoid bone abnormalities, when sufficiently severe, may contribute to persistent instability despite a well-performed capsulolabral repair. Recognition and understanding of these lesions is critical to both surgical decision making and execution of the surgical plan. Numerous procedures have been described to address posterior ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In contrast, posteriorly sloped bone loss occurs from erosive, repetitive, posterior loading and may not appear as distinct bone loss lesions when calculating the total area of loss on sagittal imaging. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, posteriorly sloped bone loss occurs from erosive, repetitive, posterior loading and may not appear as distinct bone loss lesions when calculating the total area of loss on sagittal imaging. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Although no consensus guidelines exist for the use of posterior glenoid augmentation procedures, several bone block procedures have been described for use in patients with clinically significant posterior bone loss. Dickens et al 12 advocate for the use of posterior glenoid reconstruction in patients with bone loss of >20% or >10% in the setting of glenoid retroversion, failed primary posterior labral repair, or incompetent or irreparable posterior capsular-labral tissue. While outcome studies after posterior bone augmentation are limited, Gilat et al 15 found that distal tibial allograft augmentation resulted in good outcomes and a reasonable complication rate in a series of 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Initially used in the context of anterior instability, this technique employs similar principles when used for the calculation of pGBL. Bone loss is calculated by dividing the width of the osseous defect by the diameter of a "perfect circle" placed on the inferior two-thirds of the glenoid [18]. It is prudent to point out that although anterior and posterior bone loss may be calculated in a similar fashion, the pathologic mechanisms differ significantly.…”
Section: Quantifying the Critical Pgblmentioning
confidence: 99%
“…Critical bone loss in posterior instability from a quantitative standpoint has not been entirely defined. In a recent review, Dickens et al [18] suggested that capsulolabral repair in isolation is inadequate in cases of pGBL >20% in the primary setting and >10% in revision cases.…”
Section: Quantifying the Critical Pgblmentioning
confidence: 99%
See 1 more Smart Citation